NON-FORMAL EDUCATION OPTIONS FOR ADDRESSING SECURITY CHALLENGES IN NORTH-EAST AND NORTH-WEST NIGERIA - Yusuf, Murtala Akanbi; Zakari, Lawali (Sanata Dharma University Yogyakarta, 2023)
The issue of Boko Haram and Banditry insurgency has been characterized by the killing, of people, abduction of school children, kidnapping for ransom, army robbery, raping, rustling of cows, destruction of houses, schools, mosques, churches, markets, security posts, health care centers, and farms has become a great security problem in northeast and northwest, Nigeria. The issue has resulted in a waste of peoples’ lives and livelihoods in the two geopolitical zones. The researchers believe that Boko haram insurgency and banditry security issues in Nigeria can be better addressed through Non-formal Education options. This study, therefore, examined how non-formal education can be explored to end insecurity challenges in the northeast and northwest Nigeria. The researchers used the Google database to get relevant journal papers. The prism technique was used to get and extract data based on the known inclusion and exclusion criteria. According to the analysis, non-formal education options can be explored to address boko haram insurgency and banditry in north-east and north-west Nigeria and if non-formal education options as described in this study are adopted, boko haram insurgency and banditry will be of the past in Nigeria.